Confinement and Exclusion: Re-Analysing the Geographical Metaphor of the Closet through Trans Experiences of Public Space - Bonté, Milan (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2025)
This article proposes to employ the well-known metaphor of the closet, prevalent in both lesbian, gay, bisexual, transgender, and intersex (LGBTI) popular cultures and in the geography of sexualities, as a prism through which to interpret the experiences of transgender individuals in everyday public spaces. By juxtaposing quantitative findings from two questionnaire-based surveys conducted in France and the United Kingdom with results from an ethnographic investigation into the daily practices of transgender people in public spaces across Paris, Rennes (France), and London (UK), the article argues for the closet to be viewed as both a methodological and a conceptual tool. Despite the challenges posed by the closet metaphor’s spatially contradictory range of implications, which defy simple cartographic representation, the closet metaphor facilitates the conceptualisation of the spatial dimensions of transphobia when applied to transgender lived experiences. Using geovisualisations based on the participants' life stories, the article highlights the coexistence within the trans closet of forms of rejection or avoidance, which can jointly exclude or confine, sometimes in the same place. The movements of exclusion and confinement inherent in the trans closet emerge as potent forces that limit access to space, impacts amplified by the intersection of multiple forms of discrimination.